E2F3 accelerates the stemness of colon cancer cells by activating the STAT3 pathway - Gao, Qingkun; An, Ke; Lv, Zhe; Wang, Yanzhao; Ding, Changmin; Huang, Wensheng (Frontiers in Oncology, 2023)
Introduction Colon cancer is one of the most prevalent malignancies and causes of cancer-related deaths worldwide. Thus, further research is required to explicate the latent molecular mechanisms and look for novel biomarkers. E2F3 has been confirmed to be an oncogene in a variety of cancers. However, the particular regulation of E2F3 in colon cancer needs further investigation. Methods The self-renewal ability was detected through a sphere formation assay. The tumorigenic ability was measured through nude mice in vivo assay. The protein expression of genes was examined through a Western blot. The expression of E2F3 in tumor tissues was detected through an IHC assay. The resistance to cisplatin was assessed through the CCK-8 assay. The cell migration and invasion abilities were measured after upregulating or suppressing E2F3 through the Transwell assay. Results Results uncovered that E2F3 was upregulated in spheroid cells. In addition, E2F3 facilitates stemness in colon cancer. Moreover, E2F3 facilitated colon cancer cell migration and invasion. Finally, it was revealed that E2F3 affected the STAT3 pathway to modulate stemness in colon cancer. E2F3 served as a promoter regulator in colon cancer, aggravating tumorigenesis and stemness in colon cancer progression through the STAT3 pathway. Conclusion E2F3 may be a useful biomarker for anticancer treatment in colon cancer.